THE EFFECTIVITY OF SPRE/R APPROACH IN IMPROVING CREATIVE WRITING OF THE STUDENTS (EFEKTIVITAS METODE SPRE/R APPROACH UNTUK MENINGKATKAN KEMAMPUAN MENULIS KREATIF MAHASISWA) - Fransori, Arinah (Universitas PGRI Sumatera Barat, 2019)
This study mainly discuss about the effectiveness of the SPRE/R approach method towards the creative writing ability of the students. The goal of this study is to determine whether or not the application of SPRE/R approach method to the improvement of creative writing ability of the students. The method which used in this research is quasi experiment. The sample of the research is 66 students in semester 4 who take Creative Writing Course. The study sample consisted of 33 Regular 4A class students (experimental group) learning to write using the SPRE/R approach method and 33 other students in the Regular 4B class (control group) learning using conventional methods. Data collection techniques with creative writing tests, while data analysis techniques are statistical techniques with t-test. The data show that the average of study result of experimental group for the initial test is 43,84 and the final test is 73,21 so that the average of student learning result has increased by 29,37. The average value of the control group for the initial test was 45.33 and the final test was 60.03 so that the average student learning outcomes increased by 14.7. From the difference in value is calculated by t test at a significant level of 95% and (df = n2 + n1-2). From the results of the calculation obtained t-count of 5.644 while t-table 1.998, thus, it can be concluded that there are significant differences.In addition, the results of this study produce output products in the form of a collection of short stories.